Studies on archaeoastronomy: Andean cosmovision, solar observatories or inti watgakuna and ancestral knowledge about astronomy from the runas of Kotosh - Rubina López, Alejandro (2024)
The research, from the archaeoastronomic perspective and anthropological philosophy, aimed to demonstrate through anthropological, archaeological and archaeoastronomic vestiges that the runas of Kotosh, from early times, dedicated themselves to observing various phenomena of the Andean sky, giving birth to a worldview and on the basis From their worldview they developed knowledge about astronomy. They built observatories or intiwatgakuna to observe the cyclical movement of the Sun. As a method, observation was used; which consisted of observing directly in the field, in situ, archaeoastronomic vestiges made up of the solar observatories built by the Kotosh runes. The philosophical method of hermeneutics was also used, which allowed us to interpret the meaning of the system of thought, knowledge and ancestral knowledge that these factual vestiges intrinsically contain. As a result, we still have these solar observatories or inti wakgakuna made up of wankas or solar clocks, muchkas, mortars, water mirrors or Andean telescopes. In conclusion, the Runas of Kotosh, for agricultural, livestock and social purposes, from very early times observing the Andean sky developed a worldview and knowledge about astronomy, for which they built observatories mainly to observe the movement of the Sun.